FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 - 2017 - Ika Ulinuha Aditia Swari, 15.05.52.0324; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of the current ratio, total asset turnover, debt to equity ratio and company size on return on assets in manufacturing companies listed on the Indonesian stock exchange in the period 2015-2017. The population in this study are Manufacturing Companies listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling with a research period of 2015 to 2017 and obtained as many as 243 companies. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the current ratio, total asset turnover, firm size have a significant effect and have a positive direction on return on assets while the debt to equity ratio does not have a significant effect and has a negative direction on return on assets.